A Novel Case of Transient Right Ventricular Failure in a Patient With Respiratory Distress. (May 2013) - Liu, Stanley S.; Kovell, Lara C.; Horne, Aaron; Chang, David; Petronis, John D.; Zakaria, Sammy
Right ventricular (RV) failure is characterized by an inability to pump blood into the pulmonary circulation and can often lead to hemodynamic instability. Common causes of RV failure include left ventricular (LV) failure, RV infarction, sepsis, cor pulmonale due to acute respiratory distress syndrome, pulmonary emboli, or pulmonary hypertension. We report the case of a 61-year-old woman with no significant pulmonary or cardiac disease who presented with hypoxic respiratory failure in the setting of opioid overdose. She remained obtunded despite naloxone treatment and required endotracheal intubation as well as norepinephrine therapy for persistent hypotension. A transthoracic echocardiogram demonstrated isolated severe RV dysfunction without any LV abnormalities. Cardiac catheterization showed no obstructive coronary artery disease, pulmonary hypertension, or elevated left atrial pressures, and chest imaging only revealed signs of aspiration. Over the next 6 days, the patient's cardiac and respiratory function improved, and a repeat echocardiogram demonstrated complete normalization of RV function. This case demonstrates a novel finding that marked, but transient, RV dysfunction can occur in the setting of acute respiratory failure.